Evaluation and self-evaluation of patients with rheumatic diseases in occupational therapy - Savković, Nada R.; Savković, Gordana (Education and Research in Health Sciences, 2023)
Introduction: Rheumatic diseases are a large and heterogeneous group of diseases whose manifestations threaten independence in daily life activities, lead to a decrease or loss of ability to work and have different functional and life prognosis. The treatment is complex, rehabilitation interventions include targeted occupational therapy procedures preceded by a detailed evaluation. The aim of this paper is to present changes in the daily occupation of patients with rheumatic diseases using methods for evaluation and self-evaluation within the methodology of occupational therapy assessment in clinical conditions. Methods: The research was conducted in 2021 in Academy of Applied Studies in Belgrade teaching bases in Belgrade on a sample formed of 8 patients with various rheumatic diseases who were included in the treatment in occupational therapy during treatment and rehabilitation. The same objective and subjective assessment methods were used at the beginning and end of treatment and rehabilitation. Results: In all subjects included in the study, pain decreased, fatigue occurred later, and active mobility increased to varying degrees. All respondents have adopted and practiced certain elements of protective positions and movements, thus making progress in the occupation sectors related to self-care and / or professional activities. Conclusion: Although self-evaluation methods are one of the starting points in the selection and dosing of occupational therapy procedures in training for safer and better performance of daily occupational performance, the progress made by patients by the end of treatment and rehabilitation was more visible through objective assessment methods than with methods for evaluation and self-evaluation.